Current Status of and Global Trends in Platelet Transfusion Refractoriness From 2004 to 2021: A Bibliometric Analysis - Liu, Ying; Zhang, Yufan; Chen, Dawei; Fu, Yongshui (Frontiers in Medicine, 2022)
Platelet transfusion refractoriness (PTR) is common in patients with hematology and oncology and is becoming an important barrier in the treatment of thrombocytopenia and hemorrhage. Bibliometrics is an effective method for identifying existing research achievements, important breakthroughs, current research hotspots, and future development trends in any given field. In recent years, research on PTR has received increasing attention, but a bibliometric analysis of this field has not yet been reported. In this study, we applied bibliometrics to analyze the existing literature on PTR research over the past 17 years. On November 1, 2021, we began a publications analysis of PTR research using the Science Citation Index Expanded of the Web of Science Core Collection with collection dates from 2004 to 2021. This research aimed to summarize the state of PTR research using Bibliometrix to identify connections between different elements (i.e., authors, institutions, countries, journals, references, and keywords) using VOS viewer analyses to visualize key topics and trends in PTR research using Cite Space and gCLUTO. The results of all 310 studies showed that the annual number of publications focused on PTR is steadily increasing, with the United States of America and Japan making significant contributions. We noted that the research group led by Dr. Sherrill J. Slichter was prominent in this field, while Estcourt Lise may become the most influential newcomer. Transfusion was the most popular journal, and Blood was the most cited journal. Using various analyses, including co-cited analysis, historiography analysis, citation burst analysis, and factorial analysis, we pointed out and discussed contributing publications. According to occurrence analysis, co-word biclustering analysis, landform map, thematic evolution, and thematic map, we believe that “activation,” “p-selection,” “CD36 deficiency,” “gene-frequencies,” “CD109,” “HPA-1,” and “beta (3) integrin” may become new trends in PTR research. The outcome of our bibliometric analyses has, for the first time, revealed profound insights into the current state and trends in PTR research. The systematic analysis provided by our study clearly demonstrates the field’s significant advancements to all researchers who are interested in a quick and comprehensive introduction to the field.